Efektivitas Model Problem Based Learning (PBL) Berbantuan Media Nearpod pada Pembelajaran Fisika untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Kelas X SMA Negeri 1 Godong - Gloria Lintang Puspitasari (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
. The study aims to determine the effectiveness of Problem Based Learning model assisted by nearpod media in physics learning to improve critical thinking skilss of grade X students at SMA Negeri 1 Godong. The populations of this study were all X grade students of SMA Negeri 1 Godong. The design used was Quasi Experimental Design with Pretest-Posttest Control Group Design. The sampling technique using cluster random sampling selected class X-6 and X-8. The research instruments used were pretest-posttest and documentation. Data analysis using independent Samples T-Test and N-Gain Test. Based on the results of the independent Samples T-Test, namely the pretest obtained a significance value of 0.198 > 0.05, it can be stated that Ho is accepted while Ha is rejected. Meanwhile, the posttest obtained a significance value of 0.00 < 0.05, so it can be stated Ha is accepted while Ho is rejected. The results of the N-Gain test analysis in the control class obtained were 0.43 and the experimental class N-Gain test obtained was 0.71. The results showed that the Problem Based Learning Model assisted by nearpod media in physics learning was effective for improving students’ critical thinking skills..